Meta‐analysis and field synopsis of genetic variants associated with the risk and severity of acute pancreatitis. Issue 1 (3rd December 2019) - van den Berg, F. F.; Kempeneers, M. A.; van Santvoort, H. C.; Zwinderman, A. H.; Issa, Y.; Boermeester, M. A.
Abstract : Background: Genetic risk factors can provide insight into susceptibility for acute pancreatitis (AP) and disease progression towards (infected) necrotizing pancreatitis and persistent organ failure. The aim of the study was to undertake a systematic review of the genetic evidence for AP. Methods: Online databases (MEDLINE, Embase, BIOSIS, Web of Science, Cochrane Library) were searched to 8 February 2018. Studies that reported on genetic associations with AP susceptibility, severity and/or complications were eligible for inclusion. Meta‐analyses were performed of variants that were reported by at least two data sources. Venice criteria and Bayesian false‐discovery probability were applied to assess credibility. Results: Ninety‐six studies reporting on 181 variants in 79 genes were identified. In agreement with previous meta‐analyses, credible associations were established for SPINK1 (odds ratio (OR) 2·87, 95 per cent c.i. 1·89 to 4·34), IL1B (OR 1·23, 1·06 to 1·42) and IL6 (OR 1·64, 1·15 to 2·32) and disease risk. In addition, two novel credible single‐nucleotide polymorphisms were identified in Asian populations: ALDH2 (OR 0·48, 0·36 to 0·64) and IL18 (OR 1·47, 1·18 to 1·82). Associations of variants in TNF, GSTP1 and CXCL8 genes with disease severity were identified, but were of low credibility. Conclusion: Genetic risk factors in genes related to trypsin activation and innate immunity appear to be associated with susceptibility to and severity of AP. Abstract : A comprehensive systematic review and meta‐analysis of the genetic evidence for acute pancreatitis was conducted, and identified credible associations of SPINK1, ALDH2, IL1B, IL6 and IL18 with the risk of acute pancreatitis. A lack of replication studies precludes definite conclusions to be drawn regarding the role of genetics in severity and severe clinical phenotypes of acute pancreatitis. Genes affecting trypsin activation and innate immunity important Abstract : Antecedentes: Los factores de riesgo genético pueden contribuir a determinar la susceptibilidad para desarrollar una pancreatitis aguda ( acute pancreatitis, AP) y de su progresión a pancreatitis necrotizante (infectada) e insuficiencia orgánica crónica. Nuestro objetivo fue revisar de forma sistemática la evidencia genética de la pancreatitis aguda. Métodos: Se revisaron las bases de datos electrónicas (MEDLINE, Embase, BIOSIS, Web of Science, Cochrane Library) hasta febrero de 2018. Se incluyeron estudios que presentaban información de las asociaciones genéticas y la susceptibilidad de AP, gravedad y/o complicaciones. Se realizó un metaanálisis de las variantes genéticas descritas en al menos dos fuentes. Se aplicaron los criterios de Venecia y la probabilidad bayesiana de falsa alarma para la valoración de la credibilidad. Resultados: Se identificaron 96 estudios que analizaron 181 variantes en 79 genes. De acuerdo con un metaanálisis previo, se establecieron asociaciones creibles con el riesgo de enfermedad para SPINK1 (razón de oportunidades, odds ratio, OR 2, 87, i.c. del 95% 1, 89‐4, 34), IL1B (OR 1, 23, i.c. del 95% 1, 06‐1, 42) e IL6 (OR 1, 64, i.c. del 95% 1, 15‐2, 32). Además, en poblaciones asiáticas, se identificaron dos nuevos polimorfismos de nucleótico único (SNP) creibles en ALDH2 (OR 0, 48, i.c. del 95% 0, 36‐0, 64) e IL18 (OR 1, 47, i.c. del 95% 1, 18‐1, 82). En cuanto a la gravedad de la enfermedad se identificaron variantes en los genes TNF, GSTP1 y CXCL8, pero de baja credibilidad en función de nuestra evaluación. Conclusión: Los factores de riesgo genéticos en genes relacionados con la activación de la tripsina y la inmunidad innata parecen ser estar asociados con la susceptibilidad y gravedad de la pancreatitis aguda.